2021
DOI: 10.1136/svn-2021-001024
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of bridging thrombolysis initiated before transfer in a drip-and-ship stroke service

Abstract: ObjectiveData regarding the efficacy and safety of bridging thrombolysis (BT) initiated before transfer for evaluation of endovascular therapy is heterogeneous. We, therefore, analyse efficacy and safety of BT in patients treated within a drip-and-ship stroke service.MethodsConsecutive adult patients suffering from acute ischaemic stroke and large-vessel occlusions (LVO) transferred to our comprehensive stroke centre for evaluation of endovascular therapy in 2017–2020 were identified from a local prospective s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…49 These findings were reproduced by a single-centre German study that reported higher rates of excellent functional outcome (mRS scores 0-1 or return to prestroke mRS-score) in 'drip-and-ship patients' receiving bridging therapy (23% vs. 14%). 46 There were no differences in the two groups with regard to safety outcomes including mortality and sICH. Finally, an analysis of the French Endovascular Treatment in Ischemic Stroke (ETIS) registry 50 reported that among 1,507 patients with anterior circulation LVO stroke treated with MT at three comprehensive stroke centres, 975 (64.7%) received prior IVT.…”
Section: Analysis Of Current Evidencementioning
confidence: 86%
See 2 more Smart Citations
“…49 These findings were reproduced by a single-centre German study that reported higher rates of excellent functional outcome (mRS scores 0-1 or return to prestroke mRS-score) in 'drip-and-ship patients' receiving bridging therapy (23% vs. 14%). 46 There were no differences in the two groups with regard to safety outcomes including mortality and sICH. Finally, an analysis of the French Endovascular Treatment in Ischemic Stroke (ETIS) registry 50 reported that among 1,507 patients with anterior circulation LVO stroke treated with MT at three comprehensive stroke centres, 975 (64.7%) received prior IVT.…”
Section: Analysis Of Current Evidencementioning
confidence: 86%
“…We conducted a meta-analysis of observational studies comparing direct MT with bridging therapy in drip-and-ship patients (Table 4). 46,49,50 The pooled ORs for the association between direct MT and good and excellent functional outcomes were 0.63 (95% CI: 0.48-0.83, p=0.001, Figure 10) and 0.42 (95% CI: 0.16-1.09, p=0.07, I 2 =45%, p=0.07, Figure 11), respectively. The probability of reduced disability was lower in the direct MT group compared with the bridging therapy group (adjusted cOR 0.22 [95% CI 0.07-0.69], p=0.01), but this result was based on a single study.…”
Section: Analysis Of Current Evidencementioning
confidence: 98%
See 1 more Smart Citation
“…for direct MT). 46 There were no differences in the two groups with regard to safety outcomes including mortality and sICH. Finally, an analysis of the French Endovascular Treatment in Ischemic Stroke (ETIS) registry 50 reported that among 1507 patients with anterior circulation LVO stroke treated with MT at three comprehensive stroke centers, 975 (64.7%) received prior IVT.…”
Section: Standardsmentioning
confidence: 86%
“…44 45 Finally, the proportion of LVO 'drip and ship' patients who may successfully recanalize during transfer to comprehensive centers without receiving MT is approximately nine-fold higher in bridging therapy compared with direct MT (11.7% vs 1.3%), according to the findings of a single-center German study. 46 In the French multicenter PREDICT-RECANAL study of 686 IVT-treated patients referred for MT, early recanalization (mTICI ≥2 b) after IVT was independently associated with the drip-and-ship paradigm (adjusted OR 3.3, 95% CI 1.8 to 6.0), with respective recanalization rates of 24.2% and 11.1% in drip-and-ship and mothership patients after centralized reading of arterial images. 47 Similarly, a Swiss study reported higher complete recanalization rates before MT in IVT-treated patients according to the drip-and-ship model compared with the mothership model (13.6% vs 6.2).…”
Section: Analysis Of Current Evidencementioning
confidence: 98%